Unveiling Perceptions: An Exploration of AI in Recruitment Across AI Expert, Applicant and Recruiter Perspectives - Elsaddik Valdivieso, Yasmin (Université d'Ottawa | University of Ottawa, 2024)
Navigating the challenges of talent acquisition has prompted the adoption of e-recruitment practices, driven by technological advancements. While these innovations have addressed the persistent issue of finding quality talent, the rapid pace of technological change has ushered in transformative shifts in business processes. In the pursuit of competitiveness in the war for talent, companies are increasingly turning to the implementation of AI in e-recruitment. Despite discussion in academia and literature, the perceptions surrounding this adoption remain relatively unexplored. This thesis employs a quantitative cross-sectional study conducted with AI experts, applicants, and recruiters in Canada. The empirical findings shed light on diverse approaches to AI implementation in the recruitment process, with some companies already integrating these technologies. Our methodology seeks comprehensive insights from relevant stakeholders. AI experts contribute technical knowledge and practical insights, offering crucial perspectives on the reliability of these programs. Applicants, as the primary audience for AI implementation, play a pivotal role, as their acceptance directly impacts an organization's ability to attract and retain talent. Lastly, recruiters, with their hands-on experience in the recruitment domain, provide valuable insights into the practical implications of AI tools. Research reveals that AI can be effectively applied across all stages of the recruitment process, including description, outreach, screening, assessment, selection, and communication. In the description phase AI formulates targeted job ads, outreach involves identifying and engaging both active and passive candidates. The screening phase benefits from AI's ability to match candidates to job openings, scan resumes, and rank applicants. The assessment phase applies AI through video interviews, gamified simulations, and various tests. The selection phase enables the selection of candidates based on prior stages. Finally, in communication, AI facilitates coordination and engagement with applicants through scheduling tools and Chatbot interactions. Eight scenarios were presented to quantitatively analyze the perceptions of the stakeholders. AI in the recruitment process was found to be fairer in the earlier stages than in the latter ones. Despite concerns regarding privacy, low fairness, and perceived creepiness, perceptions on organizational attractiveness remains positive throughout each scenario. This study caters to organizations uncertain about applicants' perceptions of AI integration offering valuable insight into the receptiveness of candidates additionally it serves as a practical guide for organizations considering AI implementation. The findings show that participants expressed reservations about AI's emotional intelligence driven decisions. Privacy concerns emerge as a pervasive theme prompting crucial discussion on legal and regulatory compliance. In essence this thesis contributes to an examination of AI's impact on recruitment offering insights to stakeholders' perceptions and encouraging organizations to navigate AI in recruitment.
Keywords: Recruitment Process; AI in recruitment; Perceptions towards AI; Perceptions of applicants